2017
DOI: 10.1039/c7cc03965d
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic reactivity of copper(ii)–alkylperoxo complexes

Abstract: Copper(ii)-alkylperoxo adducts, [Cu(CHDAP)(OOR)] (CHDAP = N,N'-dicyclohexyl-2,11-diaza[3,3](2,6)pyridinophane; R = C(CH)Ph and Bu), were prepared and characterized using various physicochemical methods. These are the first synthetic Cu(ii)-alkylperoxo complexes that can perform aldehyde deformylation (i.e., nucleophilic reactivity) under the stoichiometric reaction conditions, which was confirmed by kinetic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 35 publications
2
36
1
Order By: Relevance
“…3a, inset). 1-16 O 2 H exhibits two isotope sensitive bands at 834 and 501 cm −1 , which shifted to 790 and 482 cm −1 , respectively, in 1-18 O 2 H. The results support the assignments of these features as O-O and Cu-O stretching vibration on the basis of [16][17][18] Δ value of 44 and 19 cm −1 ( 16-18 Δ (calcd) = 48 and 23 cm −1 for diatomic harmonic oscillator), respectively [18][19][20][21][22][23][24] . Upon 2 H-substitution in 1, the characteristic Cu-O and O-O stretching vibrational features exhibited a 2-cm −1 downshift each ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…3a, inset). 1-16 O 2 H exhibits two isotope sensitive bands at 834 and 501 cm −1 , which shifted to 790 and 482 cm −1 , respectively, in 1-18 O 2 H. The results support the assignments of these features as O-O and Cu-O stretching vibration on the basis of [16][17][18] Δ value of 44 and 19 cm −1 ( 16-18 Δ (calcd) = 48 and 23 cm −1 for diatomic harmonic oscillator), respectively [18][19][20][21][22][23][24] . Upon 2 H-substitution in 1, the characteristic Cu-O and O-O stretching vibrational features exhibited a 2-cm −1 downshift each ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 79%
“…A bimolecular mechanism for the nucleophilic oxidative reaction by 1 is suggested by the observed negative entropy and the second-order kinetics. Compared with the reactivity of a previously reported iron(III)-hydroperoxo complex 40 and copper (II)-alkylperoxo adducts 17 , the reactivity of 1 (k 2 = 3.6 × 10 -1 M -1 s -1 at -40°C) is higher than that of the iron(III)-hydroperoxo species (k 2 = 1.3 × 10 -1 M -1 s -1 at -40°C) and those of copper(II)-alkylperoxo complexes (k 2 = 1.2-1.8 × 10 -1 M -1 s -1 at -40°C) in aldehyde deformylation of 2-PPA (Supplementary Table 7). It should be noted that the reactivity of 1 (k 2 = 3.4 M -1 s -1 at -80°C) with CCA is also higher than that of a Cu(II)-superoxo complex, [Cu(βDK)(O 2 )] -(k 2 = 1.4 M -1 s -1 at -80°C), which was a highly reactive oxidant in aldehyde deformylation reported so far (Supplementary Table 8) 41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In biological systems, metal-alkylperoxo adducts are common intermediates in a variety of oxygenase enzymes, where they can be directly involved in substrate oxidation or precede the formation of high-valent metal-oxo species. 9,10 Given the importance of metal-alkylperoxo species in such reactions, there are now many examples of synthetic Fe-, 11,12 Co-, 1,4,5 and Cu-alkylperoxo 3,13,14 adducts, and these complexes are capable of oxidizing substrates such as 1,4-cyclohexadiene, 2-phenylpropionaldehyde, and triphenylphosphine.…”
Section: Introductionmentioning
confidence: 99%
“…Mononuclear copper(II)-alkylperoxide complexes were generated by addition of alkylhydroperoxides in the presence of triethylamine (Figure 54). 229 These E AP II species were characterized by low-temperature UV–vis, CSI-MS, rRaman, and EPR. It was also found that these complexes reacted with benzoyl chloride and 2-phenylpropionaldehyde to yield the corresponding oxidation products (benzoic acid and acetophenone).…”
Section: Bioinspired Cu-promoted Oxidation Of Substrates Using O2 (Ormentioning
confidence: 99%